2016
DOI: 10.1016/j.bbrc.2016.09.114
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of brain samples from patients with Lewy body dementia

Abstract: Dementia with Lewy Bodies (DLB) is the second most common neurodegenerative disorder in the elderly. The development and progression of DLB remain unclear. In this study we used next generation sequencing to assess RNA expression profiles and cellular processes associated with DLB in the anterior cingulate cortex, a brain region affected by DLB pathology. The expression measurements were made in autopsy brain tissues from 8 DLB subjects and 10 age-matched controls using AmpliSeq technology with ion torrent seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 34 publications
4
29
2
Order By: Relevance
“…Notably, these findings occurred in a region that typically manifests relatively mild α‐synuclein deposition yet is postulated to play a central role in the cognitive profile of DLB. The reported changes differ markedly from a previous study that employed RNA‐seq in the cingulate gyrus, a region with more severe α‐synuclein pathology, and that reported genes involved in neurogenesis and myelination enriched in DLB cases when compared with controls …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Notably, these findings occurred in a region that typically manifests relatively mild α‐synuclein deposition yet is postulated to play a central role in the cognitive profile of DLB. The reported changes differ markedly from a previous study that employed RNA‐seq in the cingulate gyrus, a region with more severe α‐synuclein pathology, and that reported genes involved in neurogenesis and myelination enriched in DLB cases when compared with controls …”
Section: Discussioncontrasting
confidence: 99%
“…The reported findings are within a region with relatively low levels of Lewy body pathology and differ from those reported in a more severely affected region, the cingulate gyrus . These findings indicate important molecular changes, in addition to previously reported neuronal loss, independent of the severity of local neuropathological changes.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Meanwhile, there is a need for more hypothesis‐driven studies for replicating reported genetic associations of LBD and for exploring their functional implications. Gene expression studies and transcriptomic analyses of post‐mortem LBD brains or of circulating exosomes of people living with LBD may help understanding the functional significance of the genetic associations and their molecular networks . Future hypothesis‐driven studies should prioritise the identified genetic associations of LBD that do not overlap with known AD risk genes.…”
Section: Discussionmentioning
confidence: 99%